Robert Paine Doctor Honoris Causa - Mathiesen, Per; Thuen, Trond (Rangifer, 1998)
Professor Emeritus Dr. Robert Paine was conferred the degree of Doctor Honoris Causa at the University of Tromsø on August 27 1998 as a recognition of his long lasting and continuing influence on the anthropological study of modern society, and in particular his many contributions to the understanding of Sami reindeer husbandry and the Sami culture in general.